2024
DOI: 10.1021/acs.iecr.3c03348
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optimization of Multieffect Seawater Distillation to Gain Insights into Various Feeding Patterns: Productivity, Thermodynamic, Economic, and Environmental Perspectives

Rajdeep Mukherjee,
Ritambra Sachar,
Amiya K. Jana

Abstract: Seawater desalination is consistently gaining research interest, as water scarcity looms globally. Multieffect distillation with thermal vapor compression (MED-TVC) has emerged as a promising solution to the freshwater scarcity problem. In this contribution, we put forward a way to gain physical insights into various feeding patterns of MED-TVC and identify a suitable pattern to treat saline water effectively. For this, a dynamic model for a MED-TVC with parallel cross feed (PCF) is first formulated and then v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…As shown in Table , a very close resemblance to the plant data is obtained for the MED-TVC with a REP value of 2.3% in terms of the gain output ratio (GOR), whereas it is 2.55% for the reported model. It should be noted that this model is validated elsewhere with an additional set of plant data, whereas here we compare the MED formulation with an existing model along with a plant data set.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table , a very close resemblance to the plant data is obtained for the MED-TVC with a REP value of 2.3% in terms of the gain output ratio (GOR), whereas it is 2.55% for the reported model. It should be noted that this model is validated elsewhere with an additional set of plant data, whereas here we compare the MED formulation with an existing model along with a plant data set.…”
Section: Resultsmentioning
confidence: 99%
“…Further, MED is designed with different feeding patterns, namely forward feed (FF), backward feed (BF), parallel feed (PF), and parallel cross feed (PCF). Among them, PCF has shown better performance even under optimal operating conditions . Hence, the PCF feeding arrangement is adopted here for further advancement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike BF, the PCF does not require a pump between each pair of effects starting from the last effect along with a thick-liquor pump. According to a recent study, under optimal conditions, PCF has shown the best performance compared to the two dominant feeding patterns in seawater desalination (FF and PF). With this background report, this study has focused on the further advancement of MED-MVC having a PCF configuration.…”
Section: Introductionmentioning
confidence: 99%